Geo-radar scanning and GIS mapping of an old water utility network in Paphos District area in Cyprus under the project: 'Upgrade of the hydraulics laboratory for the modeling of water supply networks and design and operation optimization study' - Themistocleous, Kyriacos; Agapiou, Athos; Papachristodoulou, Andreas; Evlogimenos, Ploutarchos; Theodorou, Maria; Sotiropoulos, Pavlos; Maroulakis, Spyros; Karaolides, Charalambos; Hadjimitsis, Marinos Glafkou; Onoufriou, Toula; Hadjimitsis, Diofantos G. (My University, 2013)
This work is part of a research project named as 'HYDROGIS LAB'. A preliminary underground survey using the newly acquired ground penetrated radar is presented. This technology provides accurate scanning and 3D spatial representation of the underground piping network. The main aim is to refine the digital imprint of the water supply network under consideration. Work has also been initiated in the development of a GIS platform for managing all information (maps, satellite imaging, 3D scans, network system components etc). The geo-radar scanning is required to support the modeling of water supply network, design and operation.
Keywords: Geo-radar; GIS; Water utility